EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN ECOLITERACY DAN ADAPTASI (ELA) DALAM MENINGKATKAN DISIPLIN BELAJAR IPAS SISWA KELAS V SD NEGERI 1 PADOKAN - Nita Dwi Rahayu April; Hermawan Wahyu Setiadi (STKIP Subang, 2026)
This study aims to determine the differences and the effect of the use of the Ecoliteracy and Adaptation (ELA) learning model on the science learning discipline of fifth-grade students at SD Negeri 1 Padokan. The background of this study is the low level of students’ learning discipline, which is indicated by the lack of focus, responsibility, and active participation in science learning. This research employed a quasi-experimental method with a non-equivalent pretest–posttest control group design. The population consisted of 46 fifth-grade students who were divided into two classes, namely the experimental class using the ELA learning model and the control class using direct instruction. The data collection techniques included observation, interviews, and a learning discipline questionnaire administered before and after the treatment. The data were analyzed using statistical tests to determine the differences and the effect of the ELA model on students’ learning discipline. The results showed that the average pretest score of the experimental class was 39.00 and increased to 45.52 in the posttest, while the control class had an average pretest score of 35.35 which increased to 38.91 in the posttest. The result of the Independent Sample t-test showed that the value of Sig. (2-tailed) was 0.000 < 0.05, indicating a significant difference between the experimental class and the control class. Therefore, it can be concluded that the Ecoliteracy and Adaptation (ELA) learning model is effective and has a positive effect in improving the science learning discipline of fifth-grade students at SD Negeri 1 Padokan. Keywords: Ecoliteracy and Adaptation (ELA), Learning Discipline, IPAS, Elementary School